Congenital myofibroma of the pericranium - Fuchs, Juri; Günther, Patrick; Alrajab, Abdulsattar; El Damaty, Ahmed; Antonopoulos, Wiebke; Volk, Patrick (Journal of pediatric surgery, 2020)
We report a case of a healthy male newborn with a congenital tumor of the pericranium. Imaging procedures were inconclusive concerning dignity and intracranial tumor infiltration and slow tumor growth was observed. MRI Scan raised suspicion of an intracranial tumor. Only via ultrasound, integrity of the scull could be confirmed and intracranial expansion was ruled out. Complete tumor excision was performed. Histopathological evaluation of the tumor showed a myofibroma that was resected in toto with negative resection margins.